Comparative Analysis of the Effectiveness of Coub-Douglas, Real Business Cycle, and Keynsian Growth Models in Determining Economic Growth in Nigeria - Okolo, Chimaobi Valentine; Attamah, Nicholas (Journal of Empirical Studies, 2017)
Choosing the most suited growth theory in determining output in Nigeria has been a problem for researchers and policy maker. They have been faced with the question of what drive growth of the Nigerian economy: output derived from supply of capital (savings), or output derived from aggregate demand (spending) or due to shock to technology? This study empirically examined the relative effectiveness of the Cobb-Douglas Production function, the Real Business Cycle model and the Keynesian model to determine growth drivers of the Nigerian economy. Error correction model and vector error correction model was used to examine the relative effectiveness of the three growth models in determining output in Nigeria. The result of the study showed that only the coefficient of technology significantly determined economic growth in Nigeria using the Cobb-Douglas production function. Capital and labour significantly determined gross domestic product in Nigeria in the third year, adopting the vector error correction for the Real Business Cycle model. The Keynesian model proved most significant as all explanatory variables, such a consumption expenditure, investment, government spending and balance of payment were significant determinants of Nigerian economic growth. The explanatory variables jointly contributed the most (58.43%) to the variation in the gross domestic product of Nigeria. Real gross domestic product had positive autonomous growth in the Keynesian model but negative autonomous growth using the other two models. Technology input in production should be boosted by increasing government expenditure in education/ enhanced skill acquisition and the employment of more graduates in the productive sectors of the economy. Researchers and policy makers should henceforth adopt the Keynesian growth model as the most suited for the Nigerian economy.